Tingkat Partisipasi dan Keberdayaan Petani Alumni Program SL-PTT (Kasus Desa Gegesik Wetan Kabupaten Cirebon) - Amatul Jalieli; Dwi Sadono (Jurnal Penyuluhan, 2013)
SL-PTT is a program of agricultural development has implemented a model of empowerment farmers by improving the quality and capacity of farmers through the acceleration of the implementation ICM technologies. This research aims to analyze the level of participation of farmers and the factors related to the level of participation and empowerment farmers who have followed SL-PTT. The research method used is a quantitative analysis with survay method and supported by the qualitative analysis method. The results showed the level of participation farmers graduated SL-PTT included high category on each stage of the program. The level of participation have correlation with the cosmopolitan of farmers, intensity of communication, the intensity following extension and the availability of agricultural information. The level of farmers empowerment have correlated with their participation and included high categories based on indicators of the ability of farmers to access information, implement ICM technology and make decisions.Keywords: SL-PTT Program, The level of participation, Farmers empowerment.